Dapatkah Siswa Sekolah Dasar Mengambil Keputusan terkait Perubahan iklim? Sebuah Penelitian Deskriptif - Sutinah, Cucun; widodo, ari; Muslim; syaodih, ernawulan (Jurnal Elementaria Edukasia, 2023)
One of the reasons why climate change is a contentious socioscientific topic is the swift advancement of research and technology. Based on sound judgment, controlling climate change becomes an urgent matter. This study intends to gain an overview of the factual circumstances of elementary school pupils' decision-making skills with reference to the subject of combating climate change. Descriptive quantitative research methodology is employed. The test is a multiple-choice test with 10 questions that were created using criteria for rational decision-making. 612 pupils at ten public elementary schools in the city of Bandung took the test offline. Descriptive statistics were used to assess the data and categorize it in accordance with the rationale for decision-making. The study's findings show that judgments about climate change are difficult for elementary school pupils to make. Most of their decisions are made using intuitive principles. This study has implications for the significance of discussing climate change with elementary school pupils and having them practice making critical decisions.